2011
DOI: 10.1148/radiol.11110156
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Elasticity Measured with Real-time Tissue Elastography Is a Marker of Portal Hypertension

Abstract: Splenic elasticity determined with RTE is the most closely associated parameter for evaluating HVPG and is useful as a clinical marker of portal hypertension and a predictive marker of gastroesophageal varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 31 publications
6
60
0
Order By: Relevance
“…Mendes et al (7) reported that portal hypertension could occur in some patients with NAFLD who show only mild or no fibrosis. Evaluation of splenic elasticity is superior to other methods for the estimation of portal hypertension (8). Portal hypertension, as measured according to splenic elasticity, has been reported (9) to occur in patients with NAFLD who have milder fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendes et al (7) reported that portal hypertension could occur in some patients with NAFLD who show only mild or no fibrosis. Evaluation of splenic elasticity is superior to other methods for the estimation of portal hypertension (8). Portal hypertension, as measured according to splenic elasticity, has been reported (9) to occur in patients with NAFLD who have milder fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic or splenic elastic ratio (elasticity of small veins and elasticity of hepatic or splenic parenchyma) was then calculated. The means of five measurements were calculated as described elsewhere (8,19). Splenic elasticity has been reported to correlate well with the hepatic venous pressure gradient (HVPG), and this value was termed the splenic elasticity for portal hypertension (SEP) score (splenic elasticity times, 1.63-2.88; r = 0.854; P , .0001) (8,9).…”
Section: Patientsmentioning
confidence: 99%
“…As reported, spleen stiffness estimated by real-time elastography, 10 FibroScan, 11 and Virtual Touch tissue quantification (VTQ; Siemens Medical Solutions, Mountain View, CA) on acoustic radiation force impulse imaging [12][13][14][15] can be used for diagnosis of liver fibrosis and portal hypertension and for predicting variceal bleeding. The novel ultrasound-based acoustic radiation force impulse imaging directly estimates tissue stiffness by measuring the speed of shear wave propagation through the tissue in the region of interest (eg, the spleen).…”
mentioning
confidence: 99%
“…The deformability of the organ (elasticity) depends on the tissue composition; neoplastic tissues have higher cell density and therefore a reduced elasticity (increased tissue stiffness) (Goddi et al, 2012). Similarly, fluids, physically, cannot be compressed and an increased blood flow in an organ increases its hardness (Hirooka et al, 2011). In human medicine, malignant parenchymal lesions are significantly stiffer than surrounding normal parenchyma (Wells & Liang, 2011;Barr, 2012;Teng et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%